Changes in Metabolism, Mitochondrial Function, and Oxidative Stress Between Female Rats Under Nonreproductive and 3 Reproductive Conditions. (January 2019) - Hyatt, Hayden W.; Zhang, Yufeng; Hood, Wendy R.; Kavazis, Andreas N.
Women who do not lactate display increased incidence of obesity, type II diabetes, and cancer. Stuebe and Rich-Edwards proposed that these effects occur because physiological changes that ensue during pregnancy are not reversed without lactation. To empirically test this hypothesis, we compared markers of metabolism, mitochondrial function, and oxidative stress between 4 groups of Sprague-Dawley rats: (1) nonreproductive (NR) rats, (2) rats killed at day 20 of gestation, (3) rats that gave birth but were not allowed to suckle their pups (nonlactating), and (4) rats that suckled their young for 14 days. Nonlactating females displayed higher body fat compared to all other groups. Peroxisome proliferator-activated receptor δ (PPARδ) in skeletal muscle and white adipose tissue of nonlactating rats was lower than the other groups. The PPARδ is associated with lipid metabolism suggesting that the higher fat mass in nonlactating females was not associated with the retention of a physiological state that was set during pregnancy but instead an independent drop in PPARδ. Relative mitochondrial respiratory function and complex activity in the liver and skeletal muscle of nonlactating mice were not predictive of higher body mass, and measures of oxidative stress displayed minimal variation between groups.